Towards a sustainable electricity grid: Market and policy for demand-side storage and wind resources. (December 2020) - Ademulegun, Oluwasola O.; Keatley, Patrick; Agbonaye, Osaru; Moreno Jaramillo, Andres F.; Hewitt, Neil J.
Abstract: While the net benefit of installing Distributed Energy Resources (DER) is largely locational, this work examines the system value in adding wind turbines and battery storage to a Northern Irish electricity distribution network. The DER – turbines and storage – were deployed in modules: first, for increased self-consumption of wind energy and secondly, for additional services. The results suggest that, given the current market structure, deploying the DER solely for increased self-consumption, while technically achievable, is not economically feasible. The upgrading approaches profitability and sustainability as the storage is deployed for stacked market services – and could be achieved through suitable market policies. Highlights: The roles that storage and wind resources could play in achieving sustainability of the electricity grid are described. The metrics for sustainability for Northern Irish electricity grid are given with respect to Net Zero emissions. The policies and the equitable market arrangements needed for supporting demand-side resources are described. Wind turbines and storage are deployed on a Northern Irish electricity distribution network as case study. The deployment approaches profitability and sustainability as the storage is deployed for stacked services.